Uveal Melanoma Cell Growth Is Inhibited by Aminoimidazole Carboxamide Ribonucleotide (AICAR) Partially Through Activation of AMP-Dependent Kinase - Al-Moujahed, Ahmad (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. To evaluate the effects and mechanism of aminoimidazole carboxamide ribonucleotide (AICAR), an AMP-dependent kinase (AMPK) activator, on the growth of uveal melanoma cell lines. METHODS. Four different cell lines were treated with AICAR (1–4 mM). Cell growth was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay. Cell cycle analysis was conducted by flow cytometry; additionally, expression of cell-cycle control proteins, cell growth transcription factors, and downstream effectors of AMPK were determined by RT-PCR and Western blot. RESULTS. Aminoimidazole carboxamide ribonucleotide inhibited cell growth, induced S-phase arrest, and led to AMPK activation. Aminoimidazole carboxamide ribonucleotide treatment was associated with inhibition of eukaryotic translation initiation factor 4E-BP1 phosphorylation, a marker of mammalian target of rapamycin (mTOR) pathway activity. Aminoimidazole carboxamide ribonucleotide treatment was also associated with downregulation of cyclins A and D, but had minimal effects on the phosphorylation of ribosomal protein S6 or levels of the macroautophagy marker LC3B. The effects of AICAR were abolished by treatment with dipyridamole, an adenosine transporter inhibitor that blocks the entry of AICAR into cells. Treatment with adenosine kinase inhibitor 5-iodotubericidin, which inhibits the conversion of AICAR to its 5′-phosphorylated ribotide 5-aminoimidazole-4-carboxamide-1-D-ribofuranosyl-5′-monophosphate (ZMP; the direct activator of AMPK), reversed most of the growth-inhibitory effects, indicating that some of AICAR's antiproliferative effects are mediated at least partially through AMPK activation. CONCLUSIONS. Aminoimidazole carboxamide ribonucleotide inhibited uveal melanoma cell proliferation partially through activation of the AMPK pathway and downregulation of cyclins A1 and D1.